MANASIKA VEGAS: THEIR CAUSES, EFFECTS AND PSYCHO SPIRITUAL TREATMENT - Sridevi, G.; Dash, Sinuruddha (International Journal of Ayurveda and Pharma Research, 2015)
Manasika Vega is the intensification of Dharaniya Vega Kama, Krodha, Lobha, Mada, Matsarya, etc. This happens due to the intensification of Raga and Dvesha, which is triggered by the vitiation of Rajas and Tamas due to Asatmyaendriyartha Samyoga, Prajnaparadha and Parinama. When Raga and Dvesha get intensified, it leads to strengthening of desires, which in turn leads to a series of associated emotions of anger, fear, greed, delusion, etc. Scriptures identify Manasika Vega as a disease in themselves because they affect the functioning and health of the mind when left unchecked and divert the mind from the purpose of life which is the pursuit of the fourfold goals of Dharma, Artha, Kama and Moksha. As a result, they cause an imbalance in the three legs of life body, mind and soul, leading to physiological diseases, psychological diseases and Vasanas, that are the impressions from previous births which affects health as well. Therefore, Ayurvedic and Allied Scriptures recommend addressing the root cause, controlling the senses, cleaning the mind and the intellect through lifestyle modification, diet and psycho spiritual practices. These practices are listed in several different scriptures at philosophical and practical levels and need regular practice to have an effect. With regular practice aimed at restoring Sattva, the third Guna that is considered the purest, Rajas and Tamas can be destroyed, leading to detachment to sensorial pleasures and a steady, well-regulated and healthy mind.